Автор:
sarahdavilaАвтор:
fiona90Автор:
wilkersonОтвет:
Объяснение:
5.
1) ((3b/(b-2))-6b/(b²-4b+4)= ((3b/(b-2))-6b/(b-2)²)=(3b*(b-2)-6b)/(b-2)²=
=(3b²-6b-6b)/(b-2)²=(3b²-12b)/(b-2)²=3b*(b-4)/(b-2)².
2) (3b*(b-4)/(b-2)²):(b-4)/(b²-4)=3b*(b-4)*(b-2)*(b+2)/((b-2)²*(b-4)=
=3b*(b+2)/(b-2).
3) 3b*(b+2)/(b-2)-(2b²+8b)/((b-2)=(3b²+6b-2b²-8b)/(b-2)=
=(b²-2b)/(b-2)=b*(b-2)/(b-2)=b.
Автор:
nikolasАвтор:
alexusДобавить свой ответ
Предмет:
МатематикаАвтор:
linaccprОтветов:
Смотреть
Предмет:
Қазақ тiлiАвтор:
gertrudisОтветов:
Смотреть
Предмет:
Українська літератураАвтор:
butterballf0wwОтветов:
Смотреть